Susceptibility of Culex pipiens (Diptera: Culicidae) field populations in Cyprus to conventional organic insecticides, Bacillus thuringiensis subsp. israelensis, and methoprene - Vasquez Christodoulou, Marlen; Violaris, Marios; Hadjivassilis, Andreas; Wirth, Margaret C (My University, 2009)
Culex pipiens pipiens L. populations on Cyprus were sampled over a 6-yr period from 2002 to 2008 to evaluate the status of insecticide resistance toward the insecticides temephos, chlorpyrifos, and permethrin and to study susceptibility levels toward the recently introduced bacterial insecticide Bacillus thuringiensis subsp. israelensis De Barjac and the juvenile hormone analog, methoprene. Susceptibility to the three conventional chemical insecticides varied between different collections, with most collections showing moderate or low resistance. The 2004 Akrotiri collection had the highest temephos resistance ratio, 167-fold at the LC95, although later sampling showed that the population returned to susceptibility after treatments stopped. Chlorpyrifos resistance was generally higher than temephos resistance. Four collections showed high resistance, and the resistance ratios of two collections were notably high with resistance ratios of 110- and 248-fold at the LC95. Three collections showed high permethrin resistance (22.5-, 23.9-, and 86.3-fold). The frequency of elevated esterase activity in populations was estimated using a filter paper test, and frequencies varied from 0.9 to 65% among collections. The levels of temephos resistance and the frequency of elevated esterases in this survey were generally lower than in earlier reports, suggesting a decline in temephos resistance. Dose-response values for B. thuringiensis subsp. israelensis covered an approximate eight-fold range, but no resistance was detected. Methoprene values showed a 4.7-fold and 16-fold range at the LC50 and LC95, respectively. Two populations showed significant resistance ratios at the LC95. These data are discussed in relation to the changes in larval control practices underway in Cyprus.
Keywords: Bacillus thuringiensis subsp. israelensis; Culex pipiens; Methoprene; Organophosphate resistance